A study on the consumptive use of water by kharif rice at Canning (West Bengal) - DAS, H.P.; CHOWDHURY , A.; GAONKAR, S. B. (MAUSAM, 1995)
Based on the data for the period from 1977 to 1992 during the kharif season. mean weekly evapotranspiration (ET) and its contribution for different phases to total evaporative loss have been worked out for kharif rice at Canning. The evapotranspiration-evaporation ratio (ET/EP) and crop coefficient (Kc) have been round to attain peak values during the flowering stage. A relationship between ET/EP and number of days from transplanting has been developed and this relationship helps in detero\ining ET from a knowledge of EP and date of transplanting. Ratio of evapotranspiration to total shortwave radiation (ET/R2) which represents the combined effect of energy balance components. also reaches its peak value during the flowering stage. Among the four different energy summation indices. the potential evapotranspiration seems to be a better parameter for identification of growth stages of the crop. Water use efficiency of kharif rice shows significant year-to-year variations.